2010
DOI: 10.1016/j.jaac.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Psychiatric Predictors to Psychosis in Velocardiofacial Syndrome: A 3-Year Follow-Up Study

Abstract: Objective-To predict prodromal psychosis in adolescents with velocardiofacial syndrome (VCFS).Method-70 youth with VCFS, 27 siblings of youth with VCFS and 25 community controls were followed from childhood (Mean age = 11.8 years) into mid-adolescence (mean age 15.0 years). Psychological tests measuring intelligence, academic achievement, learning/memory, attention and executive functioning as well as measures of parent and clinician ratings of child psychiatric functioning were completed at both time points.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(149 citation statements)
references
References 88 publications
11
135
3
Order By: Relevance
“…In particular, specific phobia presents more frequently in individuals with 22q11.2DS (22% of children and 17% of adolescents) than with other types of anxiety. 4 Similar rates have been reported by Antshel and colleagues, 6 who found that anxiety and IQ in children independently predicted prodromal psychosis symptoms at 3-year follow-up assessment. In our sample of children aged 7-15 years, the highest Spence subscale rating was for fear of physical injury, which is consistent with both studies described.…”
Section: Anterior Hippocampus Contribution To Anxietysupporting
confidence: 75%
See 2 more Smart Citations
“…In particular, specific phobia presents more frequently in individuals with 22q11.2DS (22% of children and 17% of adolescents) than with other types of anxiety. 4 Similar rates have been reported by Antshel and colleagues, 6 who found that anxiety and IQ in children independently predicted prodromal psychosis symptoms at 3-year follow-up assessment. In our sample of children aged 7-15 years, the highest Spence subscale rating was for fear of physical injury, which is consistent with both studies described.…”
Section: Anterior Hippocampus Contribution To Anxietysupporting
confidence: 75%
“…4,6,7 These include shared genetic (e.g., COMT genotypes 8 ), neural (e.g., enlarged cavum septum pellucidum and lateral ventricles 9,10 ) and cognitive (e.g., impaired executive [11][12][13][14] and attentional functions [15][16][17][18] ) traits. Major neuranatomical features of 22q11.2DS and schizophrenia centrally involve the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies found that a decrease in verbal skills accompanies the onset of psychotic disorders in 22q11DS [25][26][27][28]. Another explanation may be that clinical geneticists working at these institutional clinics are familiar with the psychiatric phenotype of this syndrome and have an enhanced index of suspicion which may contribute to a higher detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric symptoms, mainly schizophrenic disorders are among the behavioral problems frequently cited as part of the phenotype of del22q11.2 12,13. syndrome. The presence of schizophrenic symptoms has attributed to this genetic condition significant value as neurobiological research model of the genetic basis of schizophrenia, which has propelled the growing number of studies aimed at the characterization of the behavioral phenotype of this syndrome [8][9][10][11][12][13][14][15][16] . The discussion about aggravation of psychiatric disorders according to age group is still contradictory.…”
mentioning
confidence: 99%